Bibliometric Analysis of Budgetary Slack - Loso Judijanto (Westscience Press, 2026)
Budgetary slack has become an important research topic in management accounting due to its implications for budgeting effectiveness, managerial behavior, and organizational performance. Although numerous empirical studies have examined the antecedents and consequences of budgetary slack, the overall development, intellectual structure, and emerging research directions of this field remain insufficiently explored. Therefore, this study aims to provide a comprehensive bibliometric analysis of budgetary slack research by identifying publication trends, influential studies, author and institutional collaboration patterns, country contributions, and major thematic developments. Data were collected from the Scopus database using the keywords related to “budgetary slack” and analyzed using bibliometric techniques with VOSviewer. The analysis includes citation analysis, co-authorship analysis, institutional and country collaboration analysis, keyword co-occurrence analysis, and density visualization. The findings reveal that budgetary slack research is primarily centered on budget control, budgetary participation, information asymmetry, performance evaluation, and managerial behavior. Highly cited studies demonstrate the importance of behavioral accounting perspectives, particularly regarding negotiation processes, incentive systems, and managerial decision-making. Furthermore, recent research trends indicate an increasing integration of ethical considerations, trust, organizational commitment, and management control systems in explaining budgetary slack behavior. The collaboration analysis shows the growing contribution of international research networks, with Indonesia and the United States emerging as important contributors. This study contributes to the literature by mapping the evolution of budgetary slack research and identifying future research opportunities related to digital budgeting systems, sustainability-oriented control mechanisms, and technology-driven management accounting practices.